The influence of recycled concrete aggregates in pervious concrete - TAVARES,L. M. (2016)
The expansion of urban areas under constant changes in the hydrological cycle directly affects the drainage of rainwater. The problems of urban drainage become major engineering problems to be solved in order to avoid negative consequences for local populations. Another urban problem is the excessive production of construction and demolition waste (CDW), in which , even with a increasingly policy of waste management , have been an end up being thrown in inappropriate disposal sites. Alternatively aiming to a minimization of the problems presented, we propose the study of permeable concrete using recycled concrete aggregate. In this study, there were evaluated the performance of concrete by means of permeability, consistency, strength, and interface conditions of the materials . Satisfactory relationships of resistance/permeability of concrete with recycled aggregate in relation to the concrete with natural aggregates was obtained, showing their best potential.